A comprehensive assessment of the impact of a colorectal cancer screening program in a northern Italian area. Issue 3 (March 2022) - Pancheri, Serena; Pertile, Riccardo; Armelao, Franco; Rizzello, Roberto Vito; Piffer, Silvano; Zorzi, Manuel; Guzzinati, Stefano; Ferro, Antonio; Mantovani, William; de Pretis, Giovanni
Abstract: Background: The impact of a faecal immunochemical test-based colorectal cancer (CRC) screening program in terms of patient prognosis could be affected by lead-time bias, which artificially increases the survival of screen-detected patients due to the early diagnosis. Aims: To provide a description of the impact of the CRC screening program in the Trentino Region (Italy), including the Cure Fraction (CF), a prognostic indicator not affected by lead-time bias. Methods: The program started in 2008, inviting the resident population aged 50–69 years. In this retrospective cohort study, 1, 697 CRC diagnosed between 2003 and 2014 in patients aged 50–69 years were classified as pre-screening (PS), screen-detected (SD), interval cancers (IC) and not-screen-detected (NSD). We compared groups by stage at diagnosis and CF. Trends in CRC mortality were reported. Results: The proportion of stage I among SD cases was 51%, higher than PS (19%; OR 4.66, 95%CI 3.50–6.20), NSD (20.6%; OR 3.96, 95%CI 2.95–5.32) and IC (33.3%; OR 2.11, 95%CI 1.10–4.04). The CF of PS, NSD and SD cases was respectively 57% (95%CI 54–60%), 60% (95%CI 58–63%) and 93% (95%CI 89–96%). CRC mortality dropped from 40.7 to 25.6\100, 000. Conclusion: The program significantly improved the prognosis of patients, decreasing CRC mortality and incidence of advanced CRCs.